Comparison between autogenous brachial–brachial upper-arm elevated direct arteriovenous fistulas and prosthetic brachial-antecubital indirect forearm arteriovenous grafts. Issue 6 (November 2022) - Kim, Hyokee; Ahn, Sanghyun; Kim, Minseob; Chung, Chris Tae Young; Choi, Kwang woo; Ko, Hyunmin; Han, Ahram; Min, Sangil; Min, Seung-Kee; Ha, Jongwon
Objectives: The National Kidney Foundation Kidney Disease Outcomes Quality Initiative (NKF-KDOQI) guidelines recommend forearm arteriovenous grafts (AVGs) as an alternative procedure to transposed basilic vein fistulas for providing secondary access during hemodialysis. Recently, autogenous elevated brachial-brachial vein fistulas (BVE) have become increasingly popular. The aim of this study was to compare the outcomes of BVE and forearm loop AVG (AVG) for secondary access in hemodialysis. Methods: We retrospectively reviewed the medical records of patients who had received a BVE or forearm AVG at a single center from January 2015 to April 2019. In total, 19 BVE were created via two-stage operations and two via a one-stage operation; 53 forearm AVG's were performed. Results: The AVG group was twice as likely to suffer loss of primary patency compared with the BVE group (odds ratio [OR], 2.666; 95% confidence interval [CI], 1.108–6.412; p  = 0.029) per the multivariate analysis. The primary patency and primary assisted patency of the BVE group were superior those of the AVG group, except for secondary patency ( p  = 0.02, p  = 0.07, p  = 0.879, respectively). In subgroup analysis, there were no significant differences in primary, primary assisted, or secondary patency between AVG and BVE when brachial vein was used for AVG outflow. In addition, no significant differences were noted regarding the infection rate (12.5% vs 12.3%, p  = 0.331, severity >0), postoperative bleeding rate (14.5% vs 3.5%, p  = 0.191, severity >1), early thrombus rate (0.0% vs 10.5%, p  = 0.122), and early failure rate (7% vs 4.8%, p  = 0.591). Conclusions: The primary patency and primary assisted patency rates of BVE were significantly better than those observed in AVGs, but the complication rates were similar. The appropriate procedure to provide vascular access should be determined by the individual patient's condition and the surgical skill of the operating surgeon.